Reliability Aware Multiple Path Installation in Software-Defined Networking - Syed Mohsan Raza (MDPI AG, 2021)
Link failures frequently occur in communication networks, which negatively impacts network services delivery. Compared to traditional distributed networks, Software-Defined Networking (SDN) provides numerous benefits for link robustness to avoid services unavailability. To cope with link failures, the existing SDN approaches compute multiple paths and install corresponding flow rules at network switches without considering the reliability value of the primary computed path. This increases computation time, traffic overhead and end-to-end packets delay. This paper proposes a new approach called Reliability Aware Multiple Path Flow Rule (RAF) that calculates links reliability and installs minimum flow rules for multiple paths based on the reliability value of the primary path. RAF has been simulated, evaluated and compared with the existing approaches. The simulation results show that RAF performs better than the existing approaches in terms of computation overhead at the controller and reduces end-to-end packet delay and traffic overhead for flow rules installation.